Multiple Nodular Swelling in Both Upper and Lower Limbs (Journal of Bangladesh College of Physicians and Surgeons, 2014)
DOI: http://dx.doi.org/10.3329/jbcps.v32i1.21052 J Bangladesh Coll Phys Surg 2014; 32: 53-54